SISTEM ABSENSI DOSEN MENGGUNAKAN NEAR FIELD COMMUNICATION (NFC) TECHNOLOGY - NOFITA RISMAWATI (Faktor Exacta, 2016)
NFC is a wireless technology that has a high frequency (13.56MHz), which has a data transfer rate of 424 Kbits / second with a short distance or close range. This tool can be used to exchange data with a distance of about 10 cm. NFC technology is a combination of smartcard and smartcard reader embedded in the device, the device is generally a mobile device like a cell phone. The purpose of the design of this system is to build attendance system attendance following absence management faculty lecturer, as well as introducing alternative wireless technologies such as Near Field Communication (NFC), contactless transactions that are made. Software development methods used include three main parts, namely the method of analysis, design and literature. The method of analysis involves collecting data using samples, learning in the existing system, and analysis of the results of the interview devoted to the parties concerned. The design method using the approach of the Unified Modelling Language (UML). The result is a design lecturer attendance system used at the time lecturer teaching (check-in) and after teaching (check-out). And lecturer attendance management application used to manage attendance data lecturers and printing reports on a daily, weekly, monthly and yearly. Keywords: Wireless, Smartcard, NFC